Gestión administrativa en el local Comercial Granja res de la parroquia Isla de Bejucal. - Onofre Fernández, Marilyn Lissette (2023)
With increasing globalization and the passage of time, the Granja Res retail store must adopt new strategies to improve its administrative management, which will translate into benefits for its revenue and sales objectives. The implementation of more effective marketing strategies will allow customers to obtain detailed information about the products, as well as the temporary offers and discounts offered. The objective of this case study "Administrative Management in the Granja Res Commercial Premises in the Parish of Bejucal Island" is to analyze the problems that afflict the business, and by which the processes within the commercial premises are affected towards its customers, starting from theoretical bases of administration mentioned by different authors, which allow us to relate to what is currently experienced within the commercial premises. Inadequate interpersonal relations generate problems in the fulfillment of objectives, since teamwork is not being carried out correctly. This can negatively affect customer service, which can result in the loss of customers to the competition. This study used a qualitative methodology to identify and address the problem in the Granja Res store, located in the parish of Isla Bejucal. This case study is oriented through deductive research because it is based on the study of all the parties involved to give an analysis of the case, hand in hand with the qualitative method which investigates and collects information and data from lived experiences to achieve a better understanding of the problem being addressed, together with bibliographic research applying as a technique for collecting information the interview which will be conducted with the owner of the store.